Lucky To Be Alive, Luckier to Breed: Lifetime Reproduction in Weddell Seals - Alexis A. Diaz; Jay J. Rotella; Kaitlin R. Macdonald; Wenyun Zuo; Shripad Tuljapurkar (Ecology Letters, 2026)
We utilized a long‐term study of Weddell seals to compute lifetime reproductive success (LRS) distributions using a theoretical approach and an empirical approach. These comparisons are often difficult to achieve among natural populations but are important for disentangling sources of variation in lifetime measures. We performed three independent analyses: the first compared LRS and age‐at‐death distributions among populations living under different environmental conditions, the second focused on populations differing in individual heterogeneity (i.e., high or low reproductive strategy), and the third compared a theoretical LRS distribution with an empirical LRS distribution. Iceberg conditions increased the probability of LRS = 0 while individual heterogeneity had little influence on LRS distributions. Age‐at‐death distributions were also highly skewed and only early life mortality was affected by environmental condition. Our theoretical LRS distribution was strikingly similar to the empirical distribution estimated from females experiencing natural intrinsic trait variability and extrinsic environmental variability. We also examine inequality measures which show that females must be ‘lucky’ to survive past maturity and of those who do, only 74% breed. These findings contribute to ongoing research that reveals how diversity in lifetime outcomes is largely governed by chance alone.

Observations of Weddell seal (Leptonychotes weddellii) supernumerary nipples - Alissa K. Anderson; Parker M. Levinson; Avalon Conklin; Jay J. Rotella (Polar Biology, 2024)
A wide variety of nipple locations and configurations exist among pinnipeds. Like all marine mammals, pinnipeds can have supernumerary nipples that form in utero. Supernumerary nipples have been documented in several species of pinnipeds, the only taxonomic group of marine mammals with variation in nipple number. We document multiple observations ( n = 4) of female Weddell seals ( Leptonychotes weddellii ) with supernumerary nipples in Erebus Bay, Antarctica, including a female Weddell seal with four nipples that was observed nursing two pups. Intraspecific variation in the number of supernumerary nipples observed included both one and two supernumerary nipples. The majority of the observed supernumerary nipples were nursed on by pups, but lactation was unable to be confirmed. These are the first documented observations of supernumerary nipples in Weddell seals.

Connectivity between white shark populations off Central California, USA and Guadalupe Island, Mexico - Paul E. Kanive; Jay J. Rotella; Taylor K. Chapple; Scot D. Anderson; Mauricio Hoyos-Padilla; Abbott Peter Klimley; Felipe Galván-Magaña; Samantha Andrzejaczek; Barbara A. Block; Salvador J. Jorgensen (Frontiers in Marine Science, 2023)
Marine animals often move beyond national borders and exclusive economic zones resulting in a need for trans-boundary management spanning multiple national jurisdictions. Highly migratory fish vulnerable to over-exploitation require protections at international level, as exploitation practices can be disparate between adjacent countries and marine jurisdictions. In this study we collaboratively conducted an analysis of white shark connectivity between two main aggregation regions with independent population assessment and legal protection programs; one off central California, USA and one off Guadalupe Island, Mexico. We acoustically tagged 326 sub-adult and adult white sharks in central California (n=210) and in Guadalupe Island (n=116) with acoustic transmitters between 2008-2019. Of the 326 tagged white sharks, 30 (9.20%) individuals were detected at both regions during the study period. We used a Bayesian implementation of logistic regression with a binomial distribution to estimate the effect of sex, maturity, and tag location to the response variable of probability of moving from one region to the other. While nearly one in ten individuals in our sample were detected in both regions over the study period, the annual rate of trans-regional movement was low (probability of movement = 0.015 yr -1 , 95% credible interval = 0.002, 0.061). Sub-adults were more likely than adults to move between regions and sharks were more likely to move from Guadalupe Island to central California, however, sex, and year were not important factors influencing movement. This first estimation of demographic-specific trans-regional movement connecting US and Mexico aggregations with high seasonal site fidelity represents an important step to future international management and assessment of the northeastern Pacific white shark population as a whole.

First observations of Weddell seals foraging in sponges in Erebus Bay, Antarctica - Rose T. N. Foster-Dyer; Kimberly T. Goetz; Matthew H. Pinkerton; Takashi Iwata; Rachel R. Holser; Sarah A. Michael; Craig Pritchard; Simon Childerhouse; Jay Rotella; Luisa Federwisch; Daniel P. Costa; Michelle A. LaRue (Polar Biology, 2023)
Attaching cameras to marine mammals allows for first-hand observation of underwater behaviours that may otherwise go unseen. While studying the foraging behaviour of 26 lactating Weddell seals ( Leptonychotes weddellii ) in Erebus Bay during the austral spring of 2018 and 2019, we witnessed three adults and one pup investigating the cavities of Rossellidae glass sponges, with one seal visibly chewing when she removed her head from the sponge. To our knowledge, this is the first report of such behaviour. While the prey item was not identifiable, some Trematomus fish (a known Weddell seal prey) use glass sponges for shelter and in which to lay their eggs. Three of the four sponge foraging observations occurred around 13:00 (NZDT). Two of the three sponge foraging adults had higher-than-average reproductive rates, and the greatest number of previous pups of any seal in our study population, each having ten pups in 12 years. This is far higher than the study population average of three previous pups (± 2.6 SD). This novel foraging strategy may have evolved in response to changes in prey availability, and could offer an evolutionary advantage to some individuals that exploit prey resources that others may not. Our observations offer new insight into the foraging behaviours of one of the world’s most studied marine mammals. Further research on the social aspects of Weddell seal behaviour may increase our understanding of the extent and mechanisms of behavioural transfer between conspecifics. Research into the specific foraging behaviour of especially successful or experienced breeders is also warranted.

Density-related reproductive costs and natal conditions predict male life history in a highly polygynous mammal - Kyle J. Lloyd; W. Chris Oosthuizen; Jay J. Rotella; Marthán N. Bester; P.J.Nico de Bruyn (Animal Behaviour, 2023)

Investigating diverse sources of variation in the amount of time Weddell seal ( Leptonychotes weddellii ) pups spend in the water during the lactation period - Shane M. Petch; Jay J. Rotella; William A. Link; J. Terrill Paterson; Robert A. Garrott (Marine Mammal Science, 2023)
Field observations suggest that time spent in the water by Weddell seal pups during lactation varies among individuals, which could yield important developmental tradeoffs. We analyzed data from 713 pups born to 419 different mothers over 9 years to evaluate total time in the water, age at first entry, and potential sources of variation using temperature loggers attached to the rear flipper of pups. Pups first entered the water at 11–29 days of age ( M = 14.9) and spent 4–204 hr ( M = 69.3) in the water by 30 days of age. Age at first entry was earlier for pups with higher birth mass and mothers of above average reproductive experience. Total time in the water was related to maternal identity and greater for female pups and for pups that had higher birth mass, mothers of intermediate age, mothers that skipped reproduction in the previous year, and for pups that first entered the water at younger ages. Phenotypic traits explain observed variation in the development of a key life history behavior in the Weddell seal. Strong individual variation in time spent in metabolically costly swimming and diving might lead to variation in growth, energy stores, and survival and fitness outcomes.

Temporal correlations among demographic parameters are ubiquitous but highly variable across species - Rémi Fay; Sandra Hamel; Martijn van de Pol; Jean‐Michel Gaillard; Nigel G. Yoccoz; Paul Acker; Matthieu Authier; Benjamin Larue; Christie Le Coeur; Kaitlin R. Macdonald; Alex Nicol‐Harper; Christophe Barbraud; et al. (Ecology Letters, 2022)
Temporal correlations among demographic parameters can strongly influence population dynamics. Our empirical knowledge, however, is very limited regarding the direction and the magnitude of these correlations and how they vary among demographic parameters and species’ life histories. Here, we use long‐term demographic data from 15 bird and mammal species with contrasting pace of life to quantify correlation patterns among five key demographic parameters: juvenile and adult survival, reproductive probability, reproductive success and productivity. Correlations among demographic parameters were ubiquitous, more frequently positive than negative, but strongly differed across species. Correlations did not markedly change along the slow‐fast continuum of life histories, suggesting that they were more strongly driven by ecological than evolutionary factors. As positive temporal demographic correlations decrease the mean of the long‐run population growth rate, the common practice of ignoring temporal correlations in population models could lead to the underestimation of extinction risks in most species.

Evaluation of novel genomic markers for pedigree construction in an isolated population of Weddell Seals (Leptonychotes weddellii) at White Island, Antarctica - Joshua M. Miller; Erin O. Campbell; Jay J. Rotella; Kaitlin R. Macdonald; Thomas S. Gelatt; Corey S. Davis (Conservation Genetics Resources, 2022)

Nutrient sources for offspring formation: diet–mother and mother–offspring isotope discrimination in domesticated gallinaceous birds - Kyle A. Cutting; Jay J. Rotella; Emma Grusing; James A. Waxe; Erika Nunlist; Bok F. Sowell (Isotopes in Environmental and Health Studies, 2021)

Influence of age and individual identity in the use of breeding colony habitat by male Weddell seals in Erebus Bay, Antarctica - Jamie L. Brusa; Jay J. Rotella; Robert A. Garrott (Marine Mammal Science, 2021)
Male–male contest behavior can contribute to spatial distributions of male pinnipeds during breeding seasons. To maximize breeding opportunities, the most competitive males would be expected to be surrounded by the highest numbers of reproductive‐age females. As information regarding fine‐scale spatial ecology of Weddell seals is lacking, we performed an exploratory study using kernel density analyses to evaluate age‐specific habitat use of male Weddell seals in Erebus Bay, Antarctica. Additionally, we investigated the relationship between age and number of surrounding reproductive‐age females using a competing set of regression models in a Bayesian framework that considered different functional forms of age while incorporating individual heterogeneity. As male adult Weddell seals aged, to at least 20 years, they were more likely to be found in areas associated with the greatest densities of reproductive‐age females, but individual heterogeneity also influenced the number of reproductive‐age female neighbors. The youngest males tended to haul out in offshore areas associated with better hunting, and older males tended to settle in more nearshore areas associated with more pup production. Our findings from this preliminary investigation indicate that male Weddell seal spatial behavior during the breeding season varies with age and individual and might be related to reproductive activity.

Variation in the vital rates of an Antarctic marine predator: the role of individual heterogeneity - J. Terrill Paterson; Jay. J. Rotella; William A. Link; Robert Garrott (Ecology, 2018)
Variation in life‐history traits such as lifespan and lifetime reproductive output is thought to arise, in part, due to among‐individual differences in the underlying probabilities of survival and reproduction. However, the stochastic nature of demographic processes can also generate considerable variation in fitness‐related traits among otherwise‐identical individuals. An improved understanding of life‐history evolution and population dynamics therefore depends on evaluating the relative role of each of these processes. Here, we used a 33‐yr data set with reproductive histories for 1,274 female Weddell seals from Erebus Bay, Antarctica, to assess the strength of evidence for among‐individual heterogeneity in the probabilities of survival and reproduction, while accounting for multiple other sources of variation in vital rates. Our analysis used recent advances in Bayesian model selection techniques and diagnostics to directly compare model fit and predictive power between models that included individual effects on survival and reproduction to those that did not. We found strong evidence for costs of reproduction to both survival and future reproduction, with breeders having rates of survival and subsequent reproduction that were 3% and 6% lower than rates for non‐breeders. We detected age‐related changes in the rates of survival and reproduction, but the patterns differed for the two rates. Survival rates steadily declined from 0.92 at age 7 to 0.56 at the maximal age of 31 yr. In contrast, reproductive rates increased from 0.68 at age 7 to 0.79 at age 16 and then steadily declined to 0.37 for the oldest females. Models that included individual effects explained more variation in observed life histories and had better estimated predictive power than those that did not, indicating their importance in understanding sources of variation among individuals in life‐history traits. We found that among‐individual heterogeneity in survival was small relative to that for reproduction. Our study, which found patterns of variation in vital rates that are consistent with a series of predictions from life‐history theory, is the first to provide a thorough assessment of variation in important vital rates for a long‐lived, high‐latitude marine mammal while taking full advantage of recent developments in model evaluation.

Drivers of Bromus tectorum Abundance in the Western North American Sagebrush Steppe - Tyler J. Brummer; Kimberley T. Taylor; Jay Rotella; Bruce D. Maxwell; Lisa J. Rew; Matt Lavin (Ecosystems, 2016)

Estimating apparent survival of sub-adult and adult white sharks (Carcharodon carcharias) in central California using mark-recapture methods - Paul E. Kanive; Jay J. Rotella; Salvador J. Jorgensen; Taylor K. Chapple; Scot D. Anderson; A. Peter Klimley; Barbara A. Block (Frontiers in Marine Science, 2015)

Female Weddell seals show flexible strategies of colony attendance related to varying environmental conditions - Thierry Chambert; Jay J. Rotella; Robert A. Garrott (Ecology, 2015)
Many animal life cycles involve movements among different habitats to fulfill varying resource demands. There are inherent costs associated with such movements, and the decision to leave or stay at a given location ought to be motivated by the benefits associated with potential target habitats. Because movement patterns, especially those associated with reproduction, can have important implications for the success (survival, reproduction) of individual animals, and therefore a population's dynamics, it is important to identify and understand their sources of variation (environmental and individual). Here, using a mark–recapture, multistate modeling approach, we investigated a set of a priori hypotheses regarding sources and patterns of variation in breeding‐colony attendance for Weddell seal ( Leptonychotes weddellii ) females on sabbatical from pup production. For such females, colony attendance might be motivated by predation avoidance and positive social interactions related to reproduction, but some costs, such as reduced foraging opportunities or aggressive interactions with conspecifics, might also exist. We expected these benefits and costs to vary with a female's condition and the environment. Results revealed that the probability of being absent from colonies was higher (1) in years when the extent of local sea ice was larger, (2) for the youngest and oldest individuals, and (3) for females with less reproductive experience. We also found substantial levels of residual individual heterogeneity in these rates. Based on our a priori predictions, we postulate that the decision to attend breeding colonies or not is directly influenced by an individual's physiological condition, as well as by the ice‐covered distance to good foraging areas, availability of predator‐free haul‐out sites, and the level of negative interactions with conspecifics inside colonies. Our results support the idea that in iteroparous species, and colonial animals in particular, seasonal and temporary movements from/to reproductive sites represent flexible behavioral strategies that can play an important role in coping with environmental variability.

Environmental correlates of temporary emigration for female Weddell seals and consequences for recruitment - Glenn E. Stauffer; Jay J. Rotella; Robert A. Garrott; William L. Kendall (Ecology, 2014)
In colonial‐breeding species, prebreeders often emigrate temporarily from natal reproductive colonies then subsequently return for one or more years before producing young. Variation in attendance–nonattendance patterns can have implications for subsequent recruitment. We used open robust‐design multistate models and 28 years of encounter data for prebreeding female Weddell seals ( Leptonychotes weddellii [Lesson]) to evaluate hypotheses about (1) the relationships of temporary emigration (TE) probabilities to environmental and population size covariates and (2) motivations for attendance and consequences of nonattendance for subsequent probability of recruitment to the breeding population. TE probabilities were density dependent (βˆ BPOP = 0.66, = 0.17; estimated effects [β] and standard errors of population size in the previous year) and increased when the fast‐ice edge was distant from the breeding colonies (βˆ DIST = 0.75, = 0.04; estimated effects and standard errors of distance to the sea‐ice edge in the current year on TE probability in the current year) and were strongly age and state dependent. These results suggest that trade‐offs between potential benefits and costs of colony attendance vary annually and might influence motivation to attend colonies. Recruitment probabilities were greatest for seals that consistently attended colonies in two or more years (e.g., = 0.56, SD = 0.17) and lowest for seals that never or inconsistently attended prior to recruitment (e.g., = 0.32, SD = 0.15), where denotes the mean recruitment probability (over all years) for 10‐year‐old seals for the specified prebreeder state. In colonial‐breeding seabirds, repeated colony attendance increases subsequent probability of recruitment to the adult breeding population; our results suggest similar implications for a marine mammal and are consistent with the hypothesis that prebreeders were motivated to attend reproductive colonies to gain reproductive skills or perhaps to optimally synchronize estrus through close association with mature breeding females.

Estimating nest abundance while accounting for time‐to‐event processes and imperfect detection - Guillaume Péron; Johann Walker; Jay Rotella; James E. Hines; James D. Nichols (Ecology, 2014)
Birds and their population dynamics are often used to understand and document anthropogenic effects on biodiversity. Nest success is a critical component of the breeding output of birds in different environments; but to obtain the complete picture of how bird populations respond to perturbations, we also need an estimate of nest abundance or density. The problem is that raw counts generally underestimate actual nest numbers because detection is imperfect and because some nests may fail or fledge before being subjected to detection efforts. Here we develop a state‐space superpopulation capture–recapture approach in which inference about detection probability is based on the age at first detection, as opposed to the sequence of re‐detections in standard capture–recapture models. We apply the method to ducks in which (1) the age of the nests and their initiation dates can be determined upon detection and (2) the duration of the different stages of the breeding cycle is a priori known. We fit three model variants with or without assumptions about the phenology of nest initiation dates, and use simulations to evaluate the performance of the approach in challenging situations. In an application to Blue‐winged Teal Anas discors breeding at study sites in North and South Dakota, USA, nesting stage (egg‐laying or incubation) markedly influenced nest survival and detection probabilities. Two individual covariates, one binary covariate (presence of grazing cattle at the nest site), and one continuous covariate (Robel index of vegetation), had only weak effects. We estimated that 5–10% of the total number of nests were available for detection but were missed by field crews. An additional 6–15% were never available for detection. These percentages are expected to be larger in less intense, more typical sampling designs. User‐friendly software nestAbund is provided to assist users in implementing the method.

Variability in temporary emigration rates of individually marked female Weddell seals prior to first reproduction - Glenn E. Stauffer; Jay J. Rotella; Robert A. Garrott (Oecologia, 2013)

Satellite imagery can be used to detect variation in abundance of Weddell seals (Leptonychotes weddellii) in Erebus Bay, Antarctica - Michelle A. LaRue; Jay J. Rotella; Robert A. Garrott; Donald B. Siniff; David G. Ainley; Glenn E. Stauffer; Claire C. Porter; Paul J. Morin (Polar Biology, 2011)

An evaluation of density‐dependent and density‐independent influences on population growth rates in Weddell seals - Jay J. Rotella; William A. Link; James D. Nichols; Gillian L. Hadley; Robert A. Garrott; Kelly M. Proffitt (Ecology, 2009)
Much of the existing literature that evaluates the roles of density‐dependent and density‐independent factors on population dynamics has been called into question in recent years because measurement errors were not properly dealt with in analyses. Using state–space models to account for measurement errors, we evaluated a set of competing models for a 22‐year time series of mark–resight estimates of abundance for a breeding population of female Weddell seals ( Leptonychotes weddellii ) studied in Erebus Bay, Antarctica. We tested for evidence of direct density dependence in growth rates and evaluated whether equilibrium population size was related to seasonal sea‐ice extent and the Southern Oscillation Index (SOI). We found strong evidence of negative density dependence in annual growth rates for a population whose estimated size ranged from 438 to 623 females during the study. Based on Bayes factors, a density‐dependence‐only model was favored over models that also included environmental covariates. According to the favored model, the population had a stationary distribution with a mean of 497 females (SD = 60.5), an expected growth rate of 1.10 (95% credible interval = 1.08–1.15) when population size was 441 females, and a rate of 0.90 (95% credible interval = 0.87–0.93) for a population of 553 females. A model including effects of SOI did receive some support and indicated a positive relationship between SOI and population size. However, effects of SOI were not large, and including the effect did not greatly reduce our estimate of process variation. We speculate that direct density dependence occurred because rates of adult survival, breeding, and temporary emigration were affected by limitations on per capita food resources and space for parturition and pup‐rearing. To improve understanding of the relative roles of various demographic components and their associated vital rates to population growth rate, mark–recapture methods can be applied that incorporate both environmental covariates and the seal abundance estimates that were developed here. An improved understanding of why vital rates change with changing population abundance will only come as we develop a better understanding of the processes affecting marine food resources in the Southern Ocean.

Variation in offspring sex ratio among individual Weddell seal (Leptonychotes weddellii) females of different quality - Kelly M. Proffitt; Robert A. Garrott; Jay J. Rotella (Behavioral Ecology and Sociobiology, 2008)

Long‐term evaluation of body mass at weaning and postweaning survival rates of Weddell seals in Erebus Bay, Antarctica - Kelly M. Proffitt; Robert A. Garrott; Jay J. Rotella (Marine Mammal Science, 2008)
Variability in juvenile survival rate is expected to be an important component of the dynamics of long‐lived animal populations. Across a range of species, individual variation in juvenile body mass has been shown to be an important cause of variation in fates of juveniles. Our goal in this paper was to estimate age‐specific apparent survival rates for Weddell seals ( Leptonychotes weddellii ) in Erebus Bay, Antarctica, and to investigate hypotheses about relationships between body mass at weaning and apparent survival rate for juveniles. Mark–resighting models found average apparent juvenile survival rate (survival from weaning to age 3) was similar between males and females, and revealed positive relationships between body mass at weaning and apparent juvenile survival rate. The effects of body mass on juvenile survival rate differed between the sexes and the relationship between body mass and survival rate was stronger in males. These results indicate that the magnitude of energy transferred from mother to pup during lactation likely has important consequences on offspring survival rate and maternal fitness.

Using form analysis techniques to improve photogrammetric mass‐estimation methods - Kelly M. Proffitt; Robert A. Garrott; Jay J. Rotella; Subhash Lele (Marine Mammal Science, 2008)
Numerical characterization of animal body forms using elliptical Fourier decomposition may be a useful analytic technique in a variety of marine mammal investigations. Using data collected from the Weddell seal ( Leptonychotes weddellii ), we describe the method of body form characterization using elliptical Fourier analysis and demonstrated usefulness of the technique in photogrammetric mass‐estimation modeling. We compared photogrammetric mass‐estimation models developed from (1) standard morphometric measurement covariates, (2) elliptical Fourier coefficient covariates, and (3) a combination of morphometric and Fourier coefficient covariates and found that mass‐estimation models employing a combination of morphometric measurements and Fourier coefficients outperformed models containing only one covariate type. Inclusion of Fourier coefficients in photogrammetric mass‐estimation models employing standard morphometric measurements reduced the width of the prediction interval by 24.4%. Increased precision of photogrammetric mass‐estimation models employing Fourier coefficients as model covariates may expand the range of ecological questions that can be addressed with estimated mass measurements.

Exploring Linkages between Abiotic Oceanographic Processes and a Top-trophic Predator in an Antarctic Ecosystem - Kelly M. Proffitt; Robert A. Garrott; Jay J. Rotella; Donald B. Siniff; J. Ward Testa (Ecosystems, 2007)

THE IMPORTANCE OF CONSIDERING PREDICTION VARIANCE IN ANALYSES USING PHOTOGRAMMETRIC MASS ESTIMATES - Kelly M. Proffitt; Robert A. Garrott; Jay J. Rotella; Jeff Banfield (Marine Mammal Science, 2007)
Development and application of photogrammetric mass‐estimation techniques in marine mammal studies is becoming increasingly common. When a photogrammetrically estimated mass is used as a covariate in regression modeling, the error associated with estimating mass induces bias in regression statistics and decreases model explanatory power. Thus, it is important to understand and account for prediction variance when addressing ecological questions that require use of estimated mass values. In a simulation study based on data collected from Weddell seals, we developed regression models of pup weaning mass as a function of maternal postparturition mass where maternal mass was directly measured and second where maternal mass was photogrammetrically estimated. We demonstrate that when estimated mass was used, the regression coefficient was biased toward zero and the coefficient of determination was 30% less than the value obtained when using maternal postparturition mass obtained from direct measurement. After applying bias correction procedures, however, the regression coefficient and coefficient of determination were within 2% of their true values. To effectively use photogrammetrically estimated masses, prediction variance should be understood and accounted for in all analyses. The methods presented in this paper are effective and simple techniques to explore and account for prediction variance.

DEVELOPMENT AND APPLICATION OF A MASS‐ESTIMATION METHOD FOR WEDDELL SEALS - Darren Ireland; Robert A. Garrott; Jay Rotella; Jeff Banfield (Marine Mammal Science, 2006)
Traditional methods of acquiring mass data limit the ability to collect large samples from across populations of some pinnipeds, or to sample without great disturbance to the animals. In order to collect substantial samples of mass data from the Weddell seal ( Leptonychotes weddellii ) population in Erebus Bay, Antarctica, we developed the equipment and methods for estimating the mass of Weddell seals using digital photographs. Resulting regression models predict the mass of adult female seals to within ±13.8% of estimated mass, and ±25.9% of estimated mass for pups. We show the protocols developed are repeatable and efficient enough to be applied to a large number of animals in a relatively short period of time and may be useful for studies of other marine mammals. We caution that prediction intervals exist around mass estimates and must be accounted for when estimates are applied to biological questions. In a limited application of the method, differences in mass transfer between experienced and inexperienced maternal females and their pups were detected when prediction error variance around mass estimates was explicitly included. Similar mass‐estimation methods may therefore be useful in consideration of biological questions requiring large samples of mass previously unattainable.

Population size estimation in Yellowstone wolves with error‐prone noninvasive microsatellite genotypes - Scott Creel; Goran Spong; Jennifer L. Sands; Jay Rotella; Janet Zeigle; Lawrence Joe; Kerry M. Murphy; Douglas Smith (Molecular Ecology, 2003)
Determining population sizes can be difficult, but is essential for conservation. By counting distinct microsatellite genotypes, DNA from noninvasive samples (hair, faeces) allows estimation of population size. Problems arise because genotypes from noninvasive samples are error‐prone, but genotyping errors can be reduced by multiple polymerase chain reaction (PCR). For faecal genotypes from wolves in Yellowstone National Park, error rates varied substantially among samples, often above the ‘worst‐case threshold’ suggested by simulation. Consequently, a substantial proportion of multilocus genotypes held one or more errors, despite multiple PCR. These genotyping errors created several genotypes per individual and caused overestimation (up to 5.5‐fold) of population size. We propose a ‘matching approach’ to eliminate this overestimation bias.

Biophysical Factors, Land Use, and Species Viability in and around Nature Reserves - Andrew J. Hansen; Jay J. Rotella (Conservation Biology, 2002)
Many nature reserves are located in landscapes with extreme biophysical conditions. We examined the effects of interactions between biophysical factors and land use on bird population viability inside and outside of Yellowstone National Park. Our hypotheses were as follows: (1) biophysical factors constrain bird species richness and bird reproduction at higher elevations; (2) nature reserves are located at higher elevations, whereas private lands and more intense land use occur mostly at lower elevations with more mild climates and fertile soils; and (3) intense land use at lower elevations favors nest predators and brood parasites and thereby reduces reproductive output for some bird species. We used simulation models to evaluate whether favorable habitats outside reserves are population source areas and whether intense land use can convert these habitats to population sinks and reduce population viability within reserves. Bird species richness and abundance were high in small hotspots in productive, low‐elevation habitats. Length of breeding season—and opportunity for renesting—was greatest at the lowest elevations for both American Robins ( Turdus migratorius ) and Yellow Warblers ( Dendroica petechia ). Nature reserves were higher in elevation than private lands, so hotspots for bird richness and abundance occurred primarily on or near private lands, where rural residential development was concentrated. Brown‐headed Cowbirds ( Molothrus ater ) were significantly more abundant near rural homes, but nests of American Robins were not parasitized and their nest success did not differ with home density. Nests of Yellow Warblers were commonly parasitized by cowbirds, and their nest success was significantly lower near rural homes. Estimated intrinsic population growth ( λ) for American Robins suggested that low‐elevation hotspots were population source areas for this species. Estimated λ for the Yellow Warbler suggested that the entire study area was a population sink, likely due to the effects of intense land use at lower elevations and climate constraints at higher elevations. Removing the effect of land use from the simulations revealed that high‐elevation hotspots were population sinks, whereas low‐elevation hotspots were source areas. Our results are consistent with the possibility that bird‐population source areas outside nature reserves can be converted to population sinks by intense human use, thereby reducing the viability of subpopulations within reserves.